MODEL’S STRUCTURE OF THE MODERN INTERNAL ENVIRONMENT OF CIVIL BUILDINGS - Кисіль, С. С.; Абизов, В. А.; Агліуллін, Р. М. (Art and Design, 2020)
Purpose. Establishment and development the model's structure of the modern internal environment research of civil buildings in accordance with the formation hierarchical levels of it’s constituent elements. Methodology. The study is based on systemic and environmental approaches that allow us to consider the interior space of civil buildings as a hierarchically subordinate integrity. Methods of comparative, typological analysis and experimental design are also used. Results. The modern internal environment analysis of civil buildings on the basis of systemic and environmental research approaches. The interior space’s structural model of the civil buildings has been developed in order to further identify possible changes in this system, to predict its future state, trends and development prospects. A wide range of design and artistic tasks that are in the process of solving the complex formation of civil buildings the internal environment are taken into account and its direct connection with functional, socio-economic, technical, technological and environmental issues is determined. The presented model of the civil buildings internal environment in the form of three areas: architectural − construction of a functional planning structure; design − subject content of the internal environment and artistic and aesthetic − the synthesis of arts and the use of natural elements. Scientific novelty. The structure of the model of the modern internal environment of civil buildings in accordance with the revealed hierarchical levels of formation of ther constituent parts is offered. Practical significance. The developed structure of the model of the modern interior of civil buildings will be useful for the practice of design, reconstruction, modernization of the interior space and will contribute to ensuring the artistic and aesthetic expressiveness of the internal environment of civil buildings.